2019
DOI: 10.1177/1179551419883608
|View full text |Cite
|
Sign up to set email alerts
|

Premises for Cholecystokinin and Gastrin Peptides in Diabetes Therapy

Abstract: Gastrin and cholecystokinin (CCK) are classical gastrointestinal peptide hormones. Their biogenesis, structures, and intestinal secretory patterns are well-known with the striking feature that their receptor-bound 'active sites' are highly homologous and that this structure is conserved for more than 500 million years during evolution. Consequently, gastrin and CCK are agonists for the same receptor (the CCK 2 receptor). But in addition, tyrosyl O-sulphated CCK are also bound to the specific CCK 1 receptor. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 103 publications
1
14
0
Order By: Relevance
“…This observation fits well with reported glucagonostatic effects of GLP-1 receptor activation (45). However, it does contrast somewhat with the reported direct glucagonotropic actions of CCK (8), and detailed study of the overall impact of activation of GLP-1 and CCK1 receptors by [Lys 12 Pal]Ex-4/CCK in this regard is required.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This observation fits well with reported glucagonostatic effects of GLP-1 receptor activation (45). However, it does contrast somewhat with the reported direct glucagonotropic actions of CCK (8), and detailed study of the overall impact of activation of GLP-1 and CCK1 receptors by [Lys 12 Pal]Ex-4/CCK in this regard is required.…”
Section: Discussionsupporting
confidence: 78%
“…Cholecystokinin (CCK) is a hormone primarily secreted from gastrointestinal I-cells as well as neurons of the enteric and central nervous systems (8). The peptide circulates in various molecular forms, with the octapeptide CCK-8 being the smallest form to exhibit full biological activity (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, GAS, MTL, and CCK are all important gastrointestinal hormones. GAS can promote gastric emptying through stimulating gastric acid secretion, MTL can enhance gastrointestinal motility, and CCK can suppress gastric emptying by inhibiting the contraction of the esophageal sphincter (20). In this Study, the observation group had higher levels of GAS and MTL but had a lower level of CCK than the control group after the operation, demonstrating that Dex can regulate the levels of gastrointestinal hormones in patients with CC after open colectomy, thereby improving the gastrointestinal function.…”
Section: Discussionmentioning
confidence: 53%
“…However, there is much more to discover concerning the biology of gastrin than is indicated. A study has shown that gastrin stimulated islet-cell growth and insulin secretion, which is proposed as a potential drug therapy for diabetes mellitus (Rehfeld 2019 ). Besides, gastrin plays an essential role in maintaining normal blood pressure (Chen et al 2013 ) and protecting the kidney function against hypertensive injury (Gu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%